DETERMINANTS OF INDONESIA’S SUGAR IMPORT VOLUME - Tri Wahyu Chandra Utama; I Nyoman Mahaendra Yasa (CV. Adiba Aisha Amira, 2026)
Sugar is one of the strategic food commodities in Indonesia that plays an important role in fulfilling household consumption needs as well as serving as a raw material for the food and beverage industry. However, relatively low domestic sugar production has not been able to meet national demand, causing the government to continue importing sugar to maintain the availability of domestic sugar supplies. The high volume of sugar imports is driven by fluctuating international sugar prices, continuous population growth, and exchange rate fluctuations. This study aims to analyze the effect of international sugar prices, population size, and the United States dollar exchange rate on the volume of Indonesia’s refined sugar imports. This study employed a quantitative approach with an associative research design and utilized time series data covering the period 1994–2024. The study consisted of 31 observations. The data used were secondary data obtained from various official sources such as the World Bank, the Food and Agriculture Organization (FAO), the United Nations (UN), and relevant government institutions. The analytical technique applied was multiple linear regression analysis using the Ordinary Least Square (OLS) approach processed through SPSS software. The results indicate that international sugar prices, population size, and the United States dollar exchange rate simultaneously have a significant effect on Indonesia’s sugar import volume. Partially, international sugar prices have a negative and significant effect on Indonesia’s sugar import volume. Population size has a positive and significant effect on Indonesia’s sugar import volume, while the United States dollar exchange rate has a negative but insignificant effect on Indonesia’s sugar import volume. The implications of this study suggest that, first, since international prices affect sugar import volume, the government needs to improve sugarcane sector productivity and maintain the stability of domestic sugar supplies in order to suppress domestic prices and reduce import dependency. Second, population growth should be accompanied by improvements in agricultural technology and agricultural productivity to balance increasing demand. Third, exchange rate stability should remain under the authority of the central bank, considering its close relation to international transactions.